Regional Economic Outlook, November 2008, Asia and Pacific. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2008)
The November 2008 Asia and Pacific REO focuses on the difficult economic environment facing policymakers in the region. Chapter 1 provides an overview of the outlook for the region. With growth slowing, and the global financial crisis increasingly affecting the region, macroeconomic and financial policies will need to be proactive. Chapter 2 looks more closely at inflation in Asia, finding that it is increasingly imported and volatile, which raises important questions about monetary policy frameworks in the future. Chapter 3 takes a longer-term look at how the expected rapid aging of the region may affect capital flows and financial markets in the years to come.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet